Titanium alloy plate surface microcrack inhibition method based on thickness difference
By quantifying the thickness difference and adopting gradient deformation and double-step insulation technology, the problem of high local cracks in the cold rolling process of titanium alloy is solved, the batch stability and operability of titanium alloy are improved, and the production cost and cycle are reduced.
Patent Information
- Application Number
- CN202510768444.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-07-18
AI Technical Summary
The proportion of local cracks caused by thickness differences in the cold rolling process of medium and high strength titanium alloys is high, and the prior art is difficult to effectively suppress, resulting in high batch defect rate and increased production costs.
By quantifying the thickness difference between the super-thick points and the standard points, setting a critical threshold, and using gradient deformation and double-step insulation collaborative processes for heat treatment, including multi-point measurement, primary rolling, double-step insulation and re-rolling until the target thickness is reached.
The batch crack incidence rate has been significantly reduced, the product pass rate has been improved, the processing cost and repeated production cycle have been reduced, the batch crack incidence has been reduced from 18.7% to 2.8%, and the product pass rate has reached more than 96.5%.
Smart Images

Figure CN120330639A_ABST
Abstract
Description
Technical Field
[0001] The invention mainly relates to the technical field of titanium alloy preparation, and in particular to a method for suppressing micro-cracks on the surface of a titanium alloy plate based on thickness difference. Background Art
[0002] Titanium alloy strips are the most widely used materials in alloys. Their surface quality defects restrict the final production cost control. Among the surface defects, cold-rolled surface crack defects account for up to 70%. Most studies have shown that in the process of cold-rolling thin-gauge plates, the synergistic effect of uneven deformation of the hot front end processing (deviation > 5%), mill bounce (amplitude ≥ 0.1mm) and roll deflection (deflection ≥ 0.05mm / m) leads to uneven distribution of plate thickness accuracy, forming local stress concentration areas and inducing cracks. When the rolling force deviation exceeds 12%, the probability of microcrack initiation increases by 6 to 8 times, resulting in a batch defect rate of 15-20%. Although the current remedial measures such as local grinding, pickling, and surface sanding can inhibit crack propagation, they result in a processing time consumption of 50% and a material loss rate of 8-12%. At the same time, such remedial measures can only eliminate surface defects, but cannot eradicate the internal stress distortion generated during the rolling process, increase the risk of non-conformity in flaw detection, and seriously weaken product quality and economy. Therefore, controlling the surface defect rate of batches at the source is the key to low cost and short cycle of the company's sheet products.
[0003] Due to the intrinsic characteristics of the hexagonal close-packed (HCP) crystal structure, the cold working plasticity index (n=0.12-0.15) of titanium alloy plates is significantly lower than that of conventional metal materials, and the work hardening effect is prominent (hardening index ≥0.35), which makes it very easy to produce crack defects during the rolling process. Figure 2 (surface) and Figure 3 As shown in the metallographic structure of the (core) titanium alloy plate, the high-magnification structure of the crack point shows that the surface and core grain morphology and phase distribution are consistent. The reason for the initiation of cracks is that the plate is locally thick, and the titanium alloy undergoes shear-dominated failure (such as ductile fracture) during the stress process. The cracks will preferentially expand along the direction of maximum shear stress (45°) to form oblique cracks, and transverse cracks perpendicular to the rolling direction will appear. Patent document CN 103898435A discloses a method for improving surface cracks in titanium alloy plates. A spraying device is used to evenly spray aluminum wire onto the surface of the slab. The spraying thickness is 0.1 to 0.3 mm. It can be applied to finished and semi-finished plates to reduce surface cracks and grinding. The invention does not mention crack suppression during cold rolling and related countermeasures. Patent CN 118957337 A discloses a method for preparing a high-strength titanium alloy capable of suppressing cracks and a high-strength titanium alloy. The method uses SLM printing technology to obtain a high-strength, high-density titanium alloy capable of suppressing cracks, but is significantly different from the current industrial-scale production route and also does not mention a method for suppressing local cracks on the cold-rolled surface. Summary of the invention
[0004] The technical problem to be solved by the present invention is: to provide a method for suppressing surface micro-cracks of titanium alloy plates based on thickness differences, aiming to solve the problem of high proportion of local cracks caused by thickness differences during the cold rolling process of medium and high strength dual-phase titanium alloy plates.
[0005] The technical solution adopted by the present invention to solve the above technical problems: A method for suppressing surface micro-cracks of titanium alloy plates based on thickness differences, the method comprising: Step 1: Measure the thickness of the titanium alloy plate at multiple points, establish a thickness data set, and identify the over-thick points and standard points in the thickness data set; Step 2: If the proportion of over-thick points in the thickness data set exceeds the set value, roll the titanium alloy plate until the thickness difference coefficient between the over-thick points and the standard points is less than the set value; Step 3: Perform heat treatment on the titanium alloy plate after primary rolling, the heat treatment comprising: The first heat preservation stage: After the titanium alloy plate reaches the temperature and is loaded into the furnace, keep it at the temperature for 15 minutes; The gradient heating stage: Starting from the temperature , heat it at a rate of 8 - 12 °C / min to ; The second heat preservation stage: Keep it at for 10 minutes, and then cool it to room temperature with the furnace; Among them, is the melting point of the titanium alloy; Step 4: Roll the heat-treated titanium alloy plate again until the target thickness is reached.
[0006] Further, the definition of the over-thick point is: the thickness of the corresponding measurement point , is the minimum value of the thickness in the standard point , .
[0007] Further, the value of the is -0.01 - 0.05 mm.
[0008] Further, the thickness difference coefficient in Step 2 is 1.033.
[0009] Further, the reduction per rolling pass in Step 2 is , where is the alloy's ultimate deformation amount.
[0010] Further, when the heat-treated titanium alloy plate is rolled again in Step 4, the deformation amount per rolling pass is , where is the ultimate deformation amount of the titanium alloy.
[0011] Advantages and beneficial effects of the present invention: By quantifying the difference relationship between local ultra-thick points and standard points, the present invention scientifically gives the determination critical threshold, and adopts the collaborative process of "gradient deformation + double-stage heat preservation" to solve the problem of high crack ratio in the cold rolling process of medium and high strength dual-phase titanium alloy, significantly improving the batch stability and operability of difficult-to-deform and high-strength titanium alloy. Verified by industrial application, the batch crack incidence rate is reduced from 18.7% to 2.8%, and the first-pass rate of products can reach more than 96.5%, which can greatly reduce the batch processing cost and repeated production cycle. Description of the drawings
[0012] Figure 1 is a flow chart of a method for suppressing surface micro-cracks of titanium alloy plates based on thickness difference according to the invention; Figure 2 is the high-magnification structure of the points in the area near the surface crack of the titanium alloy cold plate; Figure 3 is the high-magnification structure of the points in the core area of the titanium alloy cold plate; Figure 4 is the surface condition of the Ti-6Al-4V titanium alloy finished plate in the cold rolling state under Comparative Example 1 of the present invention. Detailed implementation manners
[0013] As Figure 1 shown, a method for suppressing surface micro-cracks of titanium alloy plates based on thickness difference according to the present invention includes the following steps: Step 1, thickness distribution measurement: For each titanium alloy plate, a laser / ultrasonic thickness gauge is used to perform multi-point measurement on a single plate to obtain a thickness data set characterizing the thickness distribution characteristics , where n is not less than 16.
[0014] Step 2, thickness zone determination: Based on the measured thickness values of the plates in the thickness data set , identify the number i of ultra-thick points and the number e of standard points. The thickness of the standard point is defined as: ; the thickness of the ultra-thick point is defined as: , is the minimum thickness in the standard point , is the ultimate deformation amount of the titanium alloy, and the thickness difference coefficient is set to 1.033.
[0015] Step 3, calculate the proportion of ultra-thick points in the thickness data set , when satisfying When the sheet metal is controlled by the strategy of Step 4.
[0016] Step 4. Primary rolling process regulation: Apply a multi-pass and small-deformation rolling process to the sheet metal that meets the requirements of Step 3. The reduction per rolling pass is , and continuously roll until the thickness difference coefficient between the ultra-thick layer point and the standard measurement point ≤ 1.015.
[0017] Step 5. Gradient heat treatment of the intermediate billet using a two-stage heat preservation process. The specific process parameters are: ; Among them, is the melting point temperature value of the titanium alloy; is the first-stage heat preservation stage, is 15 min; is the gradient heating stage, and R is the heating rate in the heating section. The value of R is 8 - 12 °C / min; is the second-stage heat preservation stage, and the heat preservation time is 10 min, and then it is cooled to room temperature with the furnace.
[0018] Step 6. Roll the titanium alloy sheet again, and control the deformation amount per subsequent rolling pass within , until the target thickness is reached.
[0019] Example 1: In this example, the sheet metal is Ti-6Al-4V titanium alloy, and the nominal incoming thickness is 3.0 mm. The method for suppressing surface microcracks of titanium alloy sheet based on thickness difference described in the present invention includes the following steps: Step 1. Use an ultrasonic thickness gauge to measure the thickness at multiple points of a single sheet metal to obtain a thickness data set characterizing the thickness distribution characteristics, and identify 30 effective sample numbers.
[0020] Step 2. Based on the measured thickness values of the sheet metal in the thickness data set , identify 12 samples that meet the ultra-thick point and 18 samples that meet the standard point. The minimum thickness value among the standard points is 3.03 mm.
[0021] Step 3. The proportion of ultra-thick point samples , and execute the rolling strategy of Step 4.
[0022] Step 4. In the primary rolling process, use a multi-pass and small-deformation rolling process, with a single-pass reduction rate of 0.8% - 1.1%, and continuously roll until the difference coefficient ≤ 1.015.
[0023] Step 5. Annealing of the intermediate billet: Load the sheet metal into the furnace when it reaches the temperature. The temperature in the first stage is 680 °C, and it is heat-preserved for 15 min. In the second stage, it is heated gradientally to 825 °C (heating time 15 min), and then heat-preserved for 10 min, and then cooled to room temperature with the furnace.
[0024] Step 6: Control the rolling deformation amount at 18% - 22% for each subsequent pass until the target thickness of 1.2 mm is reached.
[0025] In this embodiment, the surface quality of the final product is good, with no cracks visible to the naked eye, and the pass rate of the final batch reaches 98.5%.
[0026] Example 2: In this embodiment, the sheet material is Ti-6Al-1.5Cr-2.5Mo titanium alloy, and the nominal thickness of the incoming material is 2.8 mm. The method for suppressing surface micro-cracks of titanium alloy sheets based on thickness difference according to the present invention includes the following steps: Step 1: Use an ultrasonic thickness gauge to measure the thickness at multiple points of a single sheet to obtain a thickness data set characterizing the thickness distribution characteristics , and identify 36 valid sample numbers.
[0027] Step 2: Based on the measured thickness values of the sheets in the thickness data set , identify 21 over-thick point sample numbers, 15 standard point sample numbers, and the minimum value within the standard points is 2.83 mm.
[0028] Step 3: The proportion of samples within the over-thick points , and execute the rolling strategy in Step 4.
[0029] Step 4: Adopt a multi-pass and small-deformation rolling process in the primary rolling process, with the reduction rate per pass being 0.7% - 1.0%, and continuously roll until the difference coefficient ≤ 1.015.
[0030] Step 5: Intermediate billet annealing: Load the furnace when the sheet reaches the temperature. The temperature in the first stage is 685°C, hold for 15 minutes, then gradually increase the temperature to 832°C in the second stage (heating time 15 minutes), and then hold for 10 minutes and then cool to room temperature with the furnace.
[0031] Step 6: Control the rolling deformation amount at 15% - 20% for each subsequent pass until the target thickness of 1.0 mm is reached.
[0032] In this embodiment, the surface quality of the final product is relatively good, with no obvious cracks visible to the naked eye, and the pass rate of the final batch reaches 97.5%.
[0033] Example 3: In this embodiment, the sheet material is Ti-6Al-6V-2Sn titanium alloy, and the nominal thickness of the incoming material is 3.5 mm. The method for suppressing surface micro-cracks of titanium alloy sheets based on thickness difference according to the present invention includes the following steps: Step 1: Use an ultrasonic thickness gauge to measure the thickness at multiple points of a single sheet to obtain a thickness data set characterizing the thickness distribution characteristics , and identify 27 valid sample numbers.
[0034] Step 2: Based on the thickness data set Among the measured values of the sheet thickness, it is identified that the number of samples meeting the ultra-thick point is 14, the number of samples meeting the standard point is 13, and the minimum value within the standard point is 3.52 mm.
[0035] Step 3: The proportion of samples of the ultra-thick points meeting the coefficient of variation , perform the rolling strategy in Step 4.
[0036] Step 4: Adopt a multi-pass and small-deformation rolling process in the primary rolling pass. The reduction per pass is 0.9% - 1.2%, and continue rolling until the coefficient of variation ≤ 1.015.
[0037] Step 5: Intermediate billet annealing: Load the furnace when the sheet reaches the temperature. The temperature in the first stage is 665 °C, keep it warm for 15 min, then gradually heat up to 805 °C in the second stage (heating time 15 min), and after keeping it warm for another 10 min, cool it in the furnace to room temperature.
[0038] Step 6: Control the rolling deformation amount at 15% - 20% for each subsequent rolling until the target thickness of 1.5 mm is reached.
[0039] In this embodiment, the surface quality of the final product is good, there are no cracks visible to the naked eye, and the passing rate of the final batch reaches 100%.
[0040] Comparative Example 1: For the sheet types in this comparative example, the nominal thickness of the incoming materials is the same as that in Example 1. Specifically, the sheet type is Ti-6Al-4V titanium alloy, the nominal thickness is 3.0 mm, and the proportion of sheets meeting the coefficient of variation in the whole batch is 30%. The rolling pass deformation amount is distributed according to 23% - 25%, and finally a finished product with a target thickness of 1.2 mm is obtained. The passing rate of the final batch in Comparative Example 1 is 75%, and 25% of the sheets induce local micro-cracks. The macroscopic morphology of the cracks is as shown in the appendix Figure 4 shown, and compared with the batch passing rate obtained by using the method described in the present invention in Example 1, it is reduced by 23.5%.
Claims
1. A method for suppressing surface microcracks of titanium alloy sheets based on thickness differences, characterized in that, The method includes: Step 1: Measure the thickness of the titanium alloy sheet at multiple points, establish a thickness data set, and identify the over-thick points and standard points in the thickness data set; Step 2: If the proportion of the over-thick points in the thickness data set exceeds the set value, roll the titanium alloy sheet until the thickness difference coefficient between the over-thick points and the standard points is less than the set value; Step 3: Perform heat treatment on the titanium alloy sheet after primary rolling, and the heat treatment includes: The first heat preservation stage: After the titanium alloy sheet reaches the appropriate temperature and is loaded into the furnace, it is heat-preserved for 15 minutes at the temperature ; Gradient temperature rise stage: Starting from the temperature , heating up at a rate of 8 - 12 °C / min to ; The second heat preservation stage: At Heat preserve for 10 min, and then cool to room temperature in the furnace; Among them, is the melting point of the titanium alloy; Step 4: Roll the heat-treated titanium alloy sheet again until the target thickness is reached.
2. A method for suppressing surface microcracks of titanium alloy sheets based on thickness differences according to claim 1, characterized in that, The definition of an extra-thick point is: the thickness at the corresponding measurement point , is the minimum thickness among the standard points, .
3. A method for suppressing surface microcracks of titanium alloy plates based on thickness differences according to claim 2, characterized in that The said value is -0.01 to 0.05 mm.
4. A method for suppressing surface microcracks of titanium alloy plates based on thickness difference according to claim 2, characterized in that The thickness difference coefficient in Step 2 is 1.
033.
5. A method for suppressing surface microcracks of a titanium alloy sheet based on thickness difference according to any one of claims 1-4, characterized in that The reduction per pass in Step 2 is , where is the ultimate deformation amount of the alloy.
6. A method for suppressing surface micro-cracks of titanium alloy plates based on thickness difference according to any one of claims 1-4, characterized in that When the heat-treated titanium alloy sheet is rolled again in Step 4, the deformation amount per rolling pass is , where is the ultimate deformation amount of the titanium alloy.
Citation Information
Patent Citations
Method for repairing surface cracks of titanium alloy plate
CN103898435A
Preparation method of high-strength titanium alloy capable of inhibiting cracks and high-strength titanium alloy
CN118957337A